Impact on Timeliness in Financial Reporting in the Case of the Indonesia Stock Exchange: Dampak pada Ketepatan Waktu dalam Pelaporan Keuangan pada Kasus di Bursa Efek Indonesia - Lidya Azaria Putri; Heri Widodo (Academia Open, 2024)
This quantitative study investigates the impact of capital structure and company size on the timeliness of financial reporting within Indonesia's industrial and real estate sectors listed on the Indonesia Stock Exchange from 2019 to 2021. Utilizing multiple regression analysis and Moderated Regression Analysis (MRA) with the Eviews program, the research finds that while capital structure does not significantly affect timeliness, company size positively influences it. However, auditor quality does not moderate either relationship. The results suggest that larger companies tend to adhere more closely to reporting deadlines, potentially due to their deeper understanding of regulations, while auditor quality does not alter this dynamic. Highlights: 1. Analyzes capital structure, company size impact on Indonesian financial reporting timeliness.2. Larger firms show significant association with timely reporting.3. Auditor quality doesn't moderate capital structure, company size influence. Keywords: Timeliness of financial reporting, Capital structure, Company size, Auditor quality, Indonesia Stock Exchange.